SANKSI TERHADAP PENYELENGGARA E-COMMERCE APABILA GAGAL DALAM MELINDUNGI DATA PRIBADI PENGGUNA - Hidayah, Achmad Rafli (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
This study focuses on imposing sanctions on e-commerce providers if they fail to protect their users’ personal data. The purpose of this study is to find out the sanctions given to e-commerce providers if they fail to protect the personal data of their users based on the legal basis in force in Indonesia. The method used is a normative juridical research method, which means that the approach used in conducting this research is by approaching, examining, concepts and related theories to examine the Perpu that can answer the legal issues in this research. This type of research is a study of legal systematics by conducting research that has the aim of identifying the meaning and basis of the existing law. The results of the study indicate that there is a legal basis that can ensnare e-commerce providers if they fail to protect their users’ personal data